Pectinose electrochemical quantitative analysis method using functional metal materials. Issue 1 (31st December 2023) - Sun, Yuqi; Zhang, Jingyu; Lian, Junbo; Ye, Haifen; Ning, Jingyuan; Wu, Peng; Xiong, Siyi; Huang, Ketao; Lou, Xiongwei
ABSTRACT: As a soluble dietary fiber, pectin has the functions of lowering cholesterol, reducing weight and improving human immunity. However, nowadays, many studies have been reported on the extraction of pectin, but few on its quantitative analysis. In this paper, graphene modified copper foam and copper sheet were used as working electrodes, respectively. Pt electrode as counter electrode and Ag/AgCl (saturated KCl solution) electrode was used as reference electrode to build electrochemical detection system. The electrochemical responses to pectinose solution were measured by voltammetry (CV) and chronoamperometry (i-t). The detection data were analyzed to develop pectinose quantitative analysis model. Results indicated that the proposed method could determine pectinose concentration in solution, and graphene modified copper foam presented better responses. The sensitivity was 0.68851A cm −2 mmol/L, the detection limit was 0.24825 mol/L. This method presents some advantages including fast response, easy operation, and low cost. It provides a new method for pectinose quantitative detection.